Statistical Analysis of the Cause and Effect Relationship Between Social Situation and Crime in Omsk Region - L. M. Shaytanova (Сибирское юридическое обозрение, 2015)
The article presents the results of a statistical study of a number of determining factors as the impact on the social environment and crime in Omsk region as the reaction to such influence. The reliable statistics data provide the author with valid estimates of correlated relations of factor and result features that characterize the criminological situation in Omsk region. The achieved results can be used by criminologists for developing recommendations and measures to combat crime at the regional and national levels.